Population balance of droplets in a pulsed disc and doughnut column with wettable internals. (6th April 2017) - Fang, Qi; Jing, Dian; Zhou, Hao; Li, Shaowei
Highlights: Three new source terms considering wettability of PDDC internals were introduced into PBE. Functions in the new source term of the PBE were experimentally measured. Correlations were proposed and applied in a simplified PBM calculation. Experimental results provided base data for the study of droplet population balance. Abstract: Population balance of droplets was studied in a square-sectioned pulsed disc and doughnut column with wettable internals. It was found that a liquid film of the dispersed phase was formed on the internals. To describe the interaction between the droplets and the liquid film, three more terms need to be added into the source term of the classic population balance equation (PBE). To determine the source term of the PBE, functions including the droplet-layer coalescence frequency, residual droplet size distribution, droplet dispersion frequency from the liquid layer, droplet breakup frequency, and daughter droplet size distribution were measured experimentally. The droplet-layer coalescence frequency increases as the pulsation intensity decreases because of the longer contacting time. The residual droplet size is around half of the original coalescing droplet and affected little by the pulsation. The droplet dispersion frequency gets higher with the increasing of the pulsation intensity or the thickness of the liquid layer. The droplet breakup frequency is positively related to the energy input and droplet size. The daughter droplet size distribution changes from inverted U-shaped to M-shaped as the pulsation intensity rises. Based on the experimental results, empirical correlations were proposed to calculate these functions. Furthermore, the correlation equations were applied in a simplified population balance model to calculate the droplet number density in the column. The predicted results agree well with the experimental data, which proved the feasibility of the correlations.